bKash vs. bank-led option: Factors influencing customer's preferences - Does it warrant voluntary-insurance-policy for rapid-growth digital-banking in Bangladesh-economy? - Akim M. Rahman (Journal of Banking and Financial Economics (JBFE), 2020)
In today's technology-driven world-economy, banking-services have been modernized where customers compete for comparative time-saving-options. Bangladesh, a developing country, is no exception. Besides traditional banking, Agent-banking, bKash, Western-Union etc. serve new-way financial-services. But, in 21st-Century business-mentality era, many factors are unpredictable. Strict laws & application can marginalize the magnitudes of Perceived-risk where developed countries are ahead of developing countries. But it does not guarantee risk-free digital-transaction where developing countries are vulnerable. It might have led a slower growth of digital-banking in countries like Bangladesh. Dealing with determinant Perceived-risk, current author proposed Voluntary-Insurance policy (Rahman, 2018) that deserves to be scrutinized. Using Factor Analysis and Hypothesis Testing on customers' opinions helps identifying factors that have undermined the growth-trend of bank-led digital. Attributes "Phone call confirmation" has influenced customer's preference using bKash. "No transaction fee" has influenced using bank-led digital. Addressing risk-factors, Voluntary-Insurance in place can ensure secured digital-banking that can enhance growth of usages digital-banking.
Keywords: C0; C1; C4; D0; D1; D9; 330; Bank-led digital; digital-transaction; bKash; Voluntary Insurance; digital-banking; percived risk-factor